Occurrence of shockable rhythm in out-of-hospital cardiac arrest over time: A report from the COSTA group. (June 2020) - Oving, Iris; de Graaf, Corina; Karlsson, Lena; Jonsson, Martin; Kramer-Johansen, Jo; Berglund, Ellinor; Hulleman, Michiel; Beesems, Stefanie G.; Koster, Rudolph W.; Olasveengen, Theresa M.; Ringh, Mattias; Claessen, Andreas; et al.
Abstract: Background: Prior research suggests that the proportion of a shockable initial rhythm in out-of-hospital cardiac arrest (OHCA) declined during the last decades. This study aims to investigate if this decline is still ongoing and explore the relationship between location of OHCA and proportion of a shockable initial rhythm as initial rhythm. Methods: We calculated the proportion of patients with a shockable initial rhythm between 2006–2015 using pooled data from the COSTA-group (Copenhagen, Oslo, Stockholm, Amsterdam). Analyses were stratified according to location of OHCA (residential vs. public). Results: A total of 19, 054 OHCA cases were included. Overall, the total proportion of cases with a shockable initial rhythm decreased from 42% to 37% ( P < 0.01) from 2006 to 2015. When stratified according to location, the proportion of cases with a shockable initial rhythm decreased for OHCAs at a residential location (34% to 27%; P = 0.03), while the proportion of a shockable initial rhythm was stable among OHCAs in public locations (59%–57%; P = 0.2). During the last years of the study period (2011–2015), the overall proportion of a shockable initial rhythm remained stable (38%–37%; P = 0.45); this was observed for both residential and public OHCA. Conclusion: We found a decline in the proportion of patients with a shockable initial rhythm in OHCAs at a residential location; this decline levelled off during the second half of the study period (2011–2015). In public locations, we observed no decline in shockable initial rhythm over time.